PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII5 SMP BABUSSALAM PEKANBARU - Nurhalisyah, Nurhalisyah; Sakur, Sakur; Heleni, Susda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to fix process and improve the student’s mathematics learning outcomes in class VII5 SMP Babussalam Pekanbaru by using Problem Based Learning (PBL) model in 2017/2018 academic year at Aljabar form material. This research is a colaborative action class research where the researcher and the teacher of matematics in class VII5 SMP Babussalam Pekanbaru were colaborated in planning, doing action, doing observation, and reflecting. The sample of this research is 16 female students of class VII5 SMP Babussalam Pekanbaru with heterogen intelligent. The instrument of data collection in this research consist of observation sheet and assessment sheet. Data collection techniques in this study consisted of observation techniques and test results of mathematics learning techniques. The analysis technique used is descriptive descriptive data analysis technique and descriptive statistical data analysis. Data obtained from the observation sheet is qualitative data and analyzed by descriptive quantitative analysis technique. Data obtained from the learning result test were analyzed by descriptive statistical analysis technique. The result of data analysis show teacher’s and student’s activity have been done very well in cycle II and weakness/deficiency that happened less from cycle I to cycle II. Implementation of PBL model enables students to observe and understand problems and can collect information related to problems given by teachers. The students 'mathematics learning outcomes also increased in UH I and UH II seen from the achievement of students' knowledge and skills and frequency distribution analysis. The results of this analysis indicate that the application of PBL model can improve the learning process and improve students' mathematics learning outcomes of students of grade VII5 SMP Babussalam Pekanbaru in 2017/2018 academic year at Aljabar form material.Key Words : Problem based learning model, mathematics learning outcomes